Design and Structural Performance Evaluation of a CNC Plasma Cutting Machine Frame - Asmara Yanto; Aga Pratama; Anrinal Anrinal; Putri Pratiwi (Jurnal Teknik Mesin, 2025)
Plasma cutting is a widely used process for cutting metal plates using a high-temperature electric arc. Conventional systems are manually operated, which limits cutting precision and efficiency. To address this, a CNC plasma cutting machine was designed with a focus on structural reliability. The machine frame was designed to support automated motion along X, Y, and Z axes, enabling precise plasma head movement. The overall machine dimensions are 3000 mm × 1500 mm × 1000 mm, with a work area of 2400 mm × 1200 mm. Structural components were modeled using CAD software and analyzed using the Finite Element Method (FEM) to evaluate deformation, stress distribution, and safety factors. The structural analysis revealed maximum displacements of 4.14 µm and 3.83 µm in the X and Y units, respectively. The highest von Mises stress was found to be 56.57 MPa on the X unit and 50.19 MPa on the Y unit. The minimum safety factors were 4.41 for the X unit and 2.36 for the Y unit, indicating a safe and robust structural design. The results confirm that the designed machine frame meets mechanical integrity requirements for automated plasma cutting operations. The low deformation and acceptable stress levels ensure cutting accuracy and operational reliability. This design may serve as a foundation for future improvements or implementation in manufacturing environments.